Beyond Material Wealth: A Conceptual Analysis of Well-being Terminology in the Quran - Ahmad Syahirul Alim; Alim, Akhmad; Hafidhuddin, Didin (Journal of Islamic Economics Literatures, 2024)
The global socio-economic disparity highlights a fundamental flaw in traditional economic welfare systems. In response, Muslim economists propose an alternative through the more comprehensive and integrative concept of Islamic welfare. This study examines welfare terminology in the Quran to investigate the foundations of this concept. Utilizing a literature study approach with thematic interpretation methods, the research demonstrates that the Quran advocates for a holistic understanding of welfare. It emphasizes the spiritual dimension as the core foundation, harmonizing material, and non-material aspects to achieve inclusive social welfare. The ultimate goals include al-Falah (success in life), al-Sa'adah (happiness), Hayatun Thayyibatun (a good life in this world), and Na'imum Muqim (eternal bliss in the afterlife). The study recommends integrating spiritual welfare into the Islamic economic system and developing measurement instruments that align with this framework. Additionally, further research is needed to explore each welfare term in the Quran in greater depth.